Tingkat Kepuasan Petani Jagung Terhadap Kinerja Penyuluh Pertanian Di Desa Marobea Kecamatan Saweriga Di Kabupaten Muna Barat - Sri Juma; Awaluddin Hamzah; Yoenita Jayadisastra (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2022)
This studied aim to determined the performance of agricultural instructors and the level of farmer satisfaction with the performance of agricultural extension workers in Marobea Village, Sawerigadi District, West Muna Regency. The location selection was done purposively by considering that Marobea Village is one of the corn center villages in West Muna. Data analysis in this study used quantitative analysis. The time of the research was carried out in June-July 2022 with a total of 27 respondents. The results showed that the performance of the instructor was categorized as quite good and the level of farmer satisfaction with the performance of the extension worker was categorized as satisfactory.